2017
DOI: 10.1111/hel.12391
|View full text |Cite
|
Sign up to set email alerts
|

Reduced infectivity of waterborne viable but nonculturable Helicobacter pylori strain SS1 in mice

Abstract: Background Helicobacter pylori infection has been consistently associated with lack of access to clean water and proper sanitation, but no studies have demonstrated that the transmission of viable but nonculturable (VBNC) H. pylori can occur from drinking contaminated water. In this study, we used a laboratory mouse model to test whether waterborne VBNC H. pylori could cause gastric infection.Materials and MethodsWe performed five mouse experiments to assess the infectivity of VBNC H. pylori in various exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…Accordingly, H. pylori enters a viable but not culturable (VBNC) state within a few days after inoculation into water, associated to morphological changes from a spiral bacillus to coccoid form. While the exposition of mice to H. pylori viable strain SS1-supplemented drinking water led to infection in mice with significant gastric inflammation after 4 weeks (Boehnke et al 2015), waterborne VBNC SS1 failed to colonize mice either through drinking water exposure or oral gavage (Boehnke et al 2017).…”
Section: 1b-2 Water and Access To Sanitary And Hygienementioning
confidence: 98%
“…Accordingly, H. pylori enters a viable but not culturable (VBNC) state within a few days after inoculation into water, associated to morphological changes from a spiral bacillus to coccoid form. While the exposition of mice to H. pylori viable strain SS1-supplemented drinking water led to infection in mice with significant gastric inflammation after 4 weeks (Boehnke et al 2015), waterborne VBNC SS1 failed to colonize mice either through drinking water exposure or oral gavage (Boehnke et al 2017).…”
Section: 1b-2 Water and Access To Sanitary And Hygienementioning
confidence: 98%
“…A recent study found that coccoid H pylori failed to induce H pylori infection in mice. Boehnke et al allowed mice to freely drink water containing coccoid H pylori (10 9 cells/L) and found that either prolonged exposure of the mice to drinking water or shortened euthanasia did not result in H pylori colonization in the mouse stomach. Further studies conducted by the aforementioned investigators revealed that even if the mice were orally administered a high concentration of coccoid H pylori (four times the aforementioned dose) in drinking water for 2 weeks, the infection could not be induced.…”
Section: Influencing Factors Of H Pylori Recrudescencementioning
confidence: 99%
“…[19][20][21][22][23] In addition, H. pylori has been reliably detected in recreational and drinking water using molecular biology techniques such as PCR and fluorescent in situ hybridization, 5,16,17,[24][25][26] and has been shown to survive in water distribution systems, likely through protection from biofilms. While the VBNC form of H. pylori has been shown to be infectious in mice via gavage 31,32 (but not in drinking water), 33 and viable, culturable H. pylori is infectious through the route of drinking water in mice. While the VBNC form of H. pylori has been shown to be infectious in mice via gavage 31,32 (but not in drinking water), 33 and viable, culturable H. pylori is infectious through the route of drinking water in mice.…”
mentioning
confidence: 99%
“…27,28 Further, H. pylori may be able to better survive in the presence of certain freshwater amebae 29 and marine zooplankton, 30 suggesting another route of survival in water. While the VBNC form of H. pylori has been shown to be infectious in mice via gavage 31,32 (but not in drinking water), 33 and viable, culturable H. pylori is infectious through the route of drinking water in mice. 34 While it is plausible that water contaminated by H. pylori is a route for the transmission of H. pylori infection, the quantities of H. pylori reported to be in drinking water and thus the risk of infection from such sources remain poorly characterized.…”
mentioning
confidence: 99%